Big Data Emerging Technology: Insights into Innovative Environment for Online Learning Resources - Huda, Miftachul; Maseleno, Andino; Atmotiyoso, Pardimin; Siregar, Maragustam; Ahmad, Roslee; Jasmi, Kamarul Azmi; Muhamad, Nasrul Hisyam Nor (International journal of emerging technologies in learning, 2018)
Digital devices like tablets, smart phones, and laptop have become increasingly raised and utilised in higher education. As a result, current trends on ICT (information and communication technology) used in education begin widely with focusing on teaching and learning. The new concept of big data in recent ICT domain extends the promising research direction on online learning and big data integration through promising content that can be tailored for each student based on the context and Internet behaviour of users in online learning. This paper aims to explore innovative design for innovative online learning in Higher education using Big Data approach. Critical review from referred journals and books was conducted using thematic analysis. This paper proposes model reference which can be implemented with the technology in teaching and learning to improve student learning environment and outcomes and to enhance students’ development, performance and achievement in learning process in higher education.